HUBUNGAN PERUBAHAN STANDAR PORSI MAKAN DENGAN SISA MAKANAN PASIEN RUMAH SAKIT HOLISTIK TAHUN 2016 (STUDI SISA NASI PADA MENU MAKAN SIANG DIET HOLISTIK) - Fatkhurohman, Fatkhurohman; Lestari, Yanesti Nuravianda; Torina, Dian Titis (GIZI INDONESIA, 2017)
The high of  plate waste in hospital showed the quality of food service that was not optimal. Purwakarta Holistic Hospital used small, medium, and lage portion standard in its food service still have problem such as the high of plate waste. The aim of this study was to understand the effect of meal’s portion standard changing on the plate waste of Holistic Hospital patients. Pre-experimental study using one group pre-post test design was done to 29 patients using convenient sampling technique.The changing of meal’s portion was done for rice from medium portion (150 g) to small (0.5 or 0.25 portion). Measurement of plate waste used weighing method. Data analysis used Wilcoxon test continued with Kendall-Tau correlation test. The results show that 65.5% of patients are 42-68 years old receiving positive diet and 34.5% are non-positive diets. At the beginning of diet, the plate waste of rice of all patients still high (27.4-64.9% waste of rice) and it significantly decrease after given in small portion, even though there are still 27.6% of patients with > 20% waste of rice. There are significant influence between the change in diet portion of patiens toward plate waste of rice (r=0.804; p<0.05). It can be concluded that the fewer portion are given to the patient’s, then plate waste will be getting smaller.